You are on page 1of 11

Copyright Ren Barrientos Page 1

MAP2302 Lecture 4C 2011-3


SUBSTITUTION METHODS
The equation
y
i
=
x +y -1
x +y -2

is neither separable nor linear. However, we may obtain a solution by means of a substitution. This section
explores substitution methods that can be used to solve certain types of differential equations. The methods
illustrated are by no means exhaustive and the goal here is simply to demonstrate the general idea behind a
substitution in the context of a limited set of first and higher order equations.
Substitutions Suggested by the Form of the Equation
Sometimes the variables in an equation occur in certain combinations that that suggest a substitution. For example
the variables x and y might appear as the combination ox +by +c throughout the equation. We call this
combination bilinear in x and y and we say that a function z(x, y) is a bilinear function
1
of x and y if
z = (ox +by +c)
For example, the function
u = sin(2x -Sy +1)
is bilinear in x and y. On the other hand,
: = x +Sy
2

is not.
We now study differential equations of the form

dy
dx
= (ax +hy +c) (1)









Example 1 Solve the equation y
i
=
1-x-
x+
.
Solution
Observe that (x, y) =
1-(x+)
x+
. This suggests that we let u = x +y. We first compute JyJx:
Ju
Jx
= 1 +
Jy
Jx
=
dy
dx
=
du
dx
-1
Substituting in the differential equation we obtain the separable equation
Ju
Jx
-1 =
1 -u
u
=
1
u
-1
Simplifying,

1
Sometimes we also say that the function has a bilinear argument.
Jy
Jx
=
Jy
Ju

Ju
Jx
= o
Ju
Jx

o
Ju
Jx
= (u) =
Ju
(u)
=
1
o
Jx
Bilinear Substitution:
The Substitution u = ax +hy +c converts equation (1) into a separable equation.
Procedure: Let u = ox +by +c and replace the original differential equation by one in the variables u anu x:
Then equation (1) becomes the separable equation:
Copyright Ren Barrientos Page 2


Ju
Jx
=
1
u


This is a separable equation:
uJu = Jx
Thus,
u
2
2
= x +c
since u = x +y,
(x +y)
2
2
= x +c
or
(x +y)
2
= 2x +k
where k = 2c.
Example 2 Solve the equation y
i
= 2 + y -2x +4 .
Solution
Let u = y -2x +4. Then
Ju
Jx
=
Jy
Jx
-2
or
Jy
Jx
= 2 +
Ju
Jx

Substituting in y
i
= 2 + y -2x +4,
2 +
Ju
Jx
= 2 + u
or
Ju
Jx
= u
Separating the variables,

Ju
u
= Jx
Integrating,
_u
-12
Ju = _Jx +c
or
2u
12
= x +c
But u = y -2x +4. Hence
2(y -2x +4)
12
= x +c
or
4y -8x +1 = (x +c)
2

where y -2x +4 u.
Example 3 Solve the equation
dx
dt
= sin(x +t) ; x(u) = n4 .
Solution
Let u = x +t. Then
Ju
Jt
=
Jx
Jt
+1 =
Jx
Jt
=
Ju
Jt
-1
Substituting in the differential equation,
Copyright Ren Barrientos Page S

Ju
Jt
-1 = sinu =
Ju
Jt
= sinu +1
which is separable:
Ju
sinu +1
= Jt
Multiplying numerator and denominator by sinu -1:
(sinu -1)
(sinu +1) (sinu -1)
Ju = Jt
(sinu -1)
(sin
2
u -1)
Ju = Jt
(1 -sinu)
cos
2
u
Ju = Jt
Dividing each term in the numerator by cos
2
u,
(sec
2
u +cos
-2
u (-sinu))Ju = Jt
Integrating,
tanu -(cos u)
-1
= t +c
or
tanu -sec u = t +c
But u = x +t. Therefore,
tan(x +t) -sec(x +t) = t +c
Finally, applying the initial condition x(u) = n4,
tan(n4 +u) -sec(n4 +u) = u +c = c = 1 - 2
Thus,
tan(x +t) -se(x +t) = t +(1 - 2)
is an implicit solution.
The previous example illustrates a point: when using transformations, one can avoid unnecessary steps by
transforming the initial conditions as well. Consider again the original transformation
u = x +t
which takes us from the t-x coordinate system to the t-u coordinate system (the variable t is being retained as the
independent variable). We need to find what u is when t = u. Since x(u) = n4, the point though which the
integral curve passes in the t-x is (u, n4). Thus, u = n4 when t = u as well and the corresponding initial
condition in the t-u plane is
u(u) =
n
4

Warning: this is just a coincidence. In general the initial condition after the transformation will be different than the original one.
In this example, we are making the substitution u(t) = x(t) +t. Hence, the initial condition remains the same only because it
is specified at t = u.
The original IVP thus becomes
Ju
sinu +1
= Jt; u(u) =
n
4

Now we may use the definite integral:
_ (sec
2
s +cos
-2
s (-sins))Js
u
n
4
= _ J
t
0

_tans -
1
cos s
]
n
4
u
= t
Copyright Ren Barrientos Page 4

_tanu -
1
cos u
] -_tan(n4) -
1
cos(n4)
] = t
Finally, substituting foru,
tan(x +t) -
1
us(x +t)
= t +(1 -2)
An Application to Wave Motion
Consider a wave that moves from left to right with speed :. At any instant t it has a definite shape y = (x, t), that
is, if we fix t, what we see is a shape frozen in time:




But now we wish to make this wave move as time evolves. How do we describe this traveling wave?
Let us make a simplifying assumption that the shape of the wave does not change, that is, it does not disperse as it
travels its course. Let us also assume that when t = u the wave looks like this:





Suppose that the wave move to the right with speed :. If this wave is shifted c units to the right then it can be
described by y = (x -c) which is just another snapshot at a later time. Setting c = :t, the traveling wave can be
represented by a function of the form
= (x -:t)
This function is bilinear in x and t and satisfies the one-dimensional wave equation:

o
2

ox
2
=
1
:
2
o
2

ot
2

This is an example of a linear partial differential equation and one which you will encounter often in your future
studies.
Exercise: show that y = Asin(x -:t) where A is an arbitrary constant satisfies the one-dimensional wave equation.
Missing Intermediate Terms
Consider the second order equation
y
ii
+2y
i
= x
This linear differential equation which may be replaced by a first order equation via the substitution
u = y
i

For then,
u
i
+2u = x
which has an integrating factor p = c
]2dx
= c
2x
. Using the method of integrating factors we have
= (x)
x

:
= (x, t)
x

Wave frozen at time t
Copyright Ren Barrientos Page S

J
Jx
(c
2x
u) = xc
2x

Integrating,
c
2x
u =
1
4
c
2x
(2x +1) +c
oi
u =
1
4
(2x +1) +cc
-2x

Since u = y
i
,
y' =
1
4
(2x +1) +cc
-2x

Integrating again to obtain y(x):
y(x) = __
1
4
(2x +1) +cc
-2x
] Jx +k
Observe that we have two arbitrary constants c anu k. This is not surprising since we originally had a second order
equation.
As we shall see, it is common practice to use subscripts to denote arbitrary constants when there is more than one of
them. The above solution may be written as
y(x) = __
1
4
(2x +1) +c
1
e
-2x
] dx +c
2

where c
1
and c
2
are arbitrary constants.
Example 4 find a solution of the equation (y'')
2
= 4y'
Solution
Let u = y'. Then
(u')
2
= 4u
or
u
i
= _2u
14

Let us solve u
i
= 2u
14
. By separation of variables,
u
-14
Ju = 2Jx
Integrating,
4
S
u
34
= 2x +k
or
u = _
S
2
x +c
1
]
43

where c
1
=
3k
4
We Integrate again to reproduce y:
y(x) = __
S
2
x +c
1
]
43
Jx +c
2

=
2
S
_w
43
Jw +c
2
wheie w =
S
2
x +c
1

Thus,
y(x) =
2
7
_
3
2
x +c
1
]
73
+c
2





Copyright Ren Barrientos Page 6

Differential Forms with Homogeneous Coefficients
We now study differential equations of the form

Jy
Jx
=
H(x, y)
N(x, y)
(2)
or their associated differential form
H(x, y)Jx -N(x, y)Jy = u
We first define the concept of homogeneous of function.

Example 5 The function (x, y) = x


2
+Sxy is homogeneous of degree 2 because
(zx, zy) = (zx)
2
+S(zx)(zy)
= z
2
x
2
+Sz
2
xy
= 2
2
(x
2
+Sxy)
= z
2
(x, y)
Example 6 The function g(x, y) = c
x
is homogeneous of degree 0 because
g(zx, zy) = c
(xx)(x)

= c
(x)()

= 2

c
x

= z
0
g(x, y)
Example 7 The function b(x, y) = x +xy is not homogeneous because
b(zx, zy) = zx +(zx)(zy)
= zx +z
2
xy
and no factoring will allow us to write this as z
k
b(x, y) for any value of k.
When equation (2) involves homogeneous functions it is possible to use another substitution which converts it to a
separable equation









Remarks: do not memorize equation (3). Go through the procedure and perform the algebra as you go along. Also, the
substitution x = :y may be used instead the procedure is the same except that the separable equation involves the variables
y and :.

Definition
A function (x, y) is homogeneous of degree k if (zx, zy) = z
k
(x, y) for any real number z such that
(zx, zy) is in the domain of .
Jy = :Jx +xJ:
H(x, :x)Jx -N(x, :x)(:Jx +xJ:) = u

1
x
Jx =
N(1, :)
H(1, :) -:N(1, :)
J:; x = u (S)
If both coefficients H(x, y) and N(x, y) in (2) are homogeneous of the same degree, then substitution y = ux
converts the differential equation into a separable equation.
Procedure: Set y = :x,
Substituting,
By the homogeneity of the functions H and N, this equation is separable and
Copyright Ren Barrientos Page 7

Example 8 Find a solution of the equation (x
2
+y
2
)Jx +2xyJy = u.
Solution
This equation is neither linear nor separable. However, notice that both coefficients are homogeneous of
degree 2.
Let y = ux. Then dy = udx +xdu. Substituting y = :x and Jy = :Jx +xJ:,
(x
2
+(:x)
2
)Jx +2x(:x)(:Jx +xJ:) = u
Using homogeneity and factoring:
x
2
(1 +:
2
)Jx +2x
2
:(:Jx +xJ:) = u
Cancelling x
2
:
(1 +:
2
)Jx +2:(:Jx +xJ:) = u
Collecting like terms:
(1 +S:
2
)Jx +2:xJ: = u
This is a separable equation:
(1 +S:
2
)Jx = -2:xJ:
Thus,
1
x
Jx = -
2:
(1 +S:
2
)
J:
Integrating,
ln|x| = -
1
3
ln(1 +3u
2
) +ln|c|
Note: we introduce ln| c| as the constant of integration. This can be done without loss of generality
because any real number may be written as the log of a positive number. Introducing ln|c| instead of just c
allows us to combine all terms and simplify our final answer.
Multiplying by S:
Sln|x| = -ln(1 +S:
2
) +Sln|c|
or
ln|x
3
| = ln_
c
3
1 +S:
2
_
Renaming c
3
to C:
ln|x
3
| = ln_
C
1 +S:
2
_
Since the ln function is monotone, this equation holds if and only if
|x
3
| = _
C
1 +S:
2
_
or
x
3
=
A
1 +S:
2

where A = _C is an arbitrary constant.
Finally, since y = ux,
u =
y
x

Hence,
x
3
=
A
1 +3[
y
x

2

is an implicit solution of the differential equation.
Example 8 Find a solution of the equation
d
d0
=
0
2

3
+0
3


Copyright Ren Barrientos Page 8

Solution
The functions H(r, 0) = r0
2
and N(r, 0) = r
3
+0
3
are homogeneous of degree 3 [verify]. Let r = u0.
Then by the product rule,
Jr
J0
= 0
J:
J0
+:
Substituting:
0
du
d0
+u =
(u0)0
2
(u0)
3
+0
3
=
0
3
:
0
3
(:
3
+1)

or
0
J:
J0
+: =
0
3
:
0
3
(:
3
+1)

which gives us the separable equation
0
J:
J0
+: =
:
:
3
+1

Combining like terms,
0
J:
J0
=
: -:(:
3
+1)
:
3
+1

Separating,

:
3
+1
-:
4
J: =
1
0
J0
or
_
1
:
+:
-4
] J: = -
1
0
J0
Integrating,
ln|:| -
1
S
:
-3
= -ln|0| +ln|c|
or
ln|u| -
1
3u
3
= ln
c
0

Exercise: show that the last solution can be expressed as
0(:) =
Ac
13
3
:
; : = r0
Example 9 (an application) An airplane leaves its port located at (b, u) and travels with a constant airspeed (that is
speed relative to the air) of :
0
. Its intended destination is located at (u,u), however, there is a northerly wind
with wind speed of magnitude w and therefore the planes course must be adjusted. Find the equation of the curve
traced by the airplanes flight path.
Solution
We assume that the pilot adjusts the aircrafts flight direction to compensate for the wind speed by
maintaining a heading that is always directed toward the origin, as shown in the figure below:












w
u


(b, u)
w
u


(b, u)
o
o
y = (x)
(x, y)
y
x
Copyright Ren Barrientos Page 9

Let (x, y) be a point on the trajectory. From the figure on the right,
Jx
Jt
= -:
0
cos o ; x(u) = b

Jy
Jt
= w -:
0
sino ; y(u) = u
Hence,
Jy
Jx
=
Jy
Jt
Jx
Jt
=
w -:
0
sino
-:
0
cos o

Also from the figure, sino = yx
2
+y
2
and cos o = xx
2
+y
2
. Hence
Jy
Jx
=
w -:
0
yx
2
+y
2
-:
0
xx
2
+y
2

Simplifying,
Jy
Jx
=
:
0
y -wx
2
+y
2
:
0
x

This equation has homogeneous functions of like degree, as can be seen if we write it thus:
Jy
Jx
=
y
x
-
w
_
1 +[
y
x

2
:
0

Let u = yx so that y = ux. Then
d
dx
= x
du
dx
+u and substitution into the equation above gives us
x
Ju
Jx
+u = u -
w1 +(u)
2
:
0

or
x
Ju
Jx
= -
w1 +u
2
:
0

Separating variables,
Ju
1 +u
2
= -
w
:
0
x
Jx
Hence,
_
Ju
1 +u
2
= -
w
:
0
_
1
x
Jx
The integral on the left is found in any table of integrals:
lnu +1 +u
2
= -
w
:
0
ln|x| +k
Substituting u = yx,
ln_
y
x
+
_
1 +[
y
x

2
_ = -
w
:
0
ln|x| +k
Applying the condition y(o) = u,
ln_
u
o
+
_
1 +_
u
o
]
2
_ = -
w
:
0
ln|o| +k
which gives us k =
w

0
ln|o|.

Copyright Ren Barrientos Page 1u

Hence, the trajectory is given by
ln_
y
x
+
_
1 +[
y
x

2
_ = -
w
:
0
ln|x| +
w
:
0
ln|o|
or
ln_
y
x
+
_
1 +[
y
x

2
_ =
w
:
0
ln
o
x

Since all arguments are nonnegative,
ln_
y
x
+
_
1 +[
y
x

2
_ =
w
u

ln
a
x

Example 10 (an application) A light source located at the origin reflects its light off a mirrored surface in such a way
that the reflected light beams are parallel to the x-axis (as shown in the figure below). Find the shape of the surface.
Solution
When light impinges on a mirror, the Law of Reflection states that the angle of incidence is equal to the
angle of reflection. Thus, in the figure below, o = [.









From these figures it is clear that tano = tan[ = y' and that
2
0 = 2o so that tan0 =
2tanu
1-tan
2
u

Since tan0 = yx we have
y
x
=
2y
i
1 -(y')
2

This is a quadratic equation in y':
y(y')
2
+2xy
i
-y = u
Solving for y':
y
i
=
-2x _4x
2
+4y
2
2y

Hence,
yy
i
= -x _x
2
+y
2

In differential form,
[x _x
2
+y
2
Jx +yJy = u
The coefficients H(x, y) = x _x
2
+y
2
and N(x, y) = y are homogeneous of degree 1. Therefore, the
substitutions y = :x or x = :y may be used to solve this equation and, as an exercise, you should proceed
with the substitution y = :x.

2
0 + = 9u and also 2o + = 9u. Therefore, 0 = 2o
(x, y)
[
o
y = (x)
0

x
y
(x, y)
[
o
y = (x)
0
Copyright Ren Barrientos Page 11

However, we are going to take a different direction because we recognize something in this equation that is
familiar. If we implicitly differentiate (x
2
+y
2
)
12
, we obtain
(x
2
+y
2
)
-
1
2(x +yy
i
)
This expression appears in the equation
yy
i
= -x _x
2
+y
2

because if we rearrange its terms, we obtain
_
yy
i
+x
x
2
+y
2
= 1
The left-hand side is exactly _JJx (x
2
+y
2
)
12
. Thus,
_
J
Jx
(x
2
+y
2
)
1
2
= 1
Integrating,
_(x
2
+y
2
)
1
2
= x +c
where c is an arbitrary constant. Simplifying,
x
2
+y
2
= (x +c )
2

or
y
2
= 2cx +c
2

we immediately recognize this to be the equation of a family of parabolas with vertex on the x-axis.
performing some more algebra give us the following final result:
y
2
= 4p(x +p)
which corresponds to a parabola with vertex at (-p, u) and focus at (u,u).